2015
DOI: 10.1089/cap.2014.0103
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Correlations in Youth with Tic Disorders

Abstract: Background: Studies have noted immunological disruptions in patients with tic disorders, including increased serum cytokine levels. This study aimed to determine whether or not cytokine levels could be correlated with tic symptom severity in patients with a diagnosed tic disorder. Methods: Twenty-one patients, ages 4-17 years (average 10.63 -2.34 years, 13 males), with a clinical diagnosis of Tourette's syndrome (TS) or chronic tic disorder (CTD), were selected based on having clinic visits that coincided with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…This may be due to a homeostasis effect under toxic stress. In a balanced system, increased IL‐4 may help fight the physical and psychological disorders (Parker‐Athill et al., 2015; Pranzatelli et al., 2017). Intuitively, acute IDPN treatment may cause impairment in the Treg cells and hence immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a homeostasis effect under toxic stress. In a balanced system, increased IL‐4 may help fight the physical and psychological disorders (Parker‐Athill et al., 2015; Pranzatelli et al., 2017). Intuitively, acute IDPN treatment may cause impairment in the Treg cells and hence immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…After intervention with NDG, tics were alleviated, and the levels of TNF-α and IL-6in the striatum and serum of rats with TS decreased. TNF-α plays an integral role in immunological responses to infection as a potent regulator of the immune system and inflammatory processes, recruiting macrophages, activating T-cells, and inducing the expression of downstream cytokines and other immune mediators during infection (28). IL-6 is an important mediator of neuroinflammation and is involved in microglial priming under neuroinflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have described increased levels of proinflammatory markers in children and adolescents with neuropsychiatric disorders, including OCD and tics (Mitchell and Goldstein 2014;Gariup et al 2015). Studies have also reported higher levels of serum TNF-a during periods of tic exacerbation (Leckman et al 2005;Parker-Athill et al 2015). Although the correlation between tic severity and high cytokine levels does not imply causation, it seems plausible to hypothesize that psychiatric symptoms could attenuate with the remission of inflammation.…”
Section: Discussionmentioning
confidence: 99%